2020
DOI: 10.1080/09537287.2020.1810759
|View full text |Cite
|
Sign up to set email alerts
|

Buyer–supplier collaboration during emerging technology development

Abstract: The purpose of this paper is to understand how buyers and suppliers collaborate during the development of emerging technologies. Using the relational view, the paper examines a high technology aerospace firm as it develops additive manufacturing technology with two suppliers. Data collected from 46 interviews with senior managers, middle managers and operational employees are triangulated using 8 focus groups and secondary company documentation. It is found that the radical novelty and high degree of technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 87 publications
0
15
0
Order By: Relevance
“…Moreover, in all three aforementioned cases, improvement in product design and encouragement for innovation was captured. This manifested itself by the further development in collaboration with suppliers at the home country to develop new products and technologies (Moradlou et al, 2020b). Proximity to the suppliers and sharing the same language and time zone were viewed as facilitating factors for enhancing the collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in all three aforementioned cases, improvement in product design and encouragement for innovation was captured. This manifested itself by the further development in collaboration with suppliers at the home country to develop new products and technologies (Moradlou et al, 2020b). Proximity to the suppliers and sharing the same language and time zone were viewed as facilitating factors for enhancing the collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it must be said that current AM technologies are still classed as emerging and perhaps lack the infrastructure capable of supporting their full potential. Such is the case for the limited pool of suppliers, usually constrained to AM machine manufacturers[ 54 , 55 ]. Similarly, although technological advances on AM systems are common in the academic field[ 56 ], systems currently in use are limited by bed size, build time, technical expertise, and post processing requirements[ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…A senior manager of an aerospace firm that have adopted AM who was recently interviewed by Moradlou et al . [ 55 ] indicated that “the technology itself is not seen as a core competency, prompting the company to partner with external organizations,” resulting in increased University Technology Centers, business lead collaborations with research (e.g., Catapult centers) or a supplier driven product and process design. Nevertheless, important differences between manufacturing experts and the rest of the surveyed professionals are still observed, suggesting that limited influence of these structures may take place in healthcare.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the increased discussion about intellectual property rights on AM's potential for direct manufacturing ( Berman, 2012 ) within the coronavirus pandemic ( Mahr and Dickel, 2020 ) presumes an increased vulnerability for a supply organisation. CAD data might contain sensitive information that has high plasticity ( Moradlou et al, 2020 ), and its control against opportunistic supplier behaviour may become difficult for a procurement organisation ( Picot, 1993 ). On the one hand, this is in line with previous research which identifies suppliers as an important risk source, but with an additional risk category caused by the value of digital information exchange (3D data) with suppliers ( Zsidisin and Wagner, 2010 ).…”
Section: Comparison Of Tm and Am: Initial Assumptions For Supply Risk...mentioning
confidence: 99%